2015
DOI: 10.5539/ijbm.v10n9p182
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Board Diversity on the Performance of Banks: Evidence from Turkey

Abstract: This study has primary two aims. The first is to determine the characteristics of boards of directors in the Turkish banking industry and the second is to investigate the effect of board diversity on performance of the banks. The analyses in this study are built on the banking industry of Turkey in the period from 2008 to 2012. The impact of the board diversity, as measured by the percentage of women and foreign directors on the board and the Blau index, on financial performance is investigated by conducting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 37 publications
7
38
1
4
Order By: Relevance
“…Ongore et al (2015), Shungu et al (2014), and Pathan et al (2013) found a positive correlation amongst the proportion of women directors and banks' performance. Conversely, Kilic (2015) found an adverse correlation between gender diversity and bank performance. Meanwhile, Liang, Xu, & Jiraporn (2013) show no significant association amongst the proportion of women on the board of directors and banks' performance.…”
Section: Board Gender and Bank Performancementioning
confidence: 92%
See 2 more Smart Citations
“…Ongore et al (2015), Shungu et al (2014), and Pathan et al (2013) found a positive correlation amongst the proportion of women directors and banks' performance. Conversely, Kilic (2015) found an adverse correlation between gender diversity and bank performance. Meanwhile, Liang, Xu, & Jiraporn (2013) show no significant association amongst the proportion of women on the board of directors and banks' performance.…”
Section: Board Gender and Bank Performancementioning
confidence: 92%
“…Firms with non-executive directors are independent, works in stakeholder's best interest, have better control over management and have a positive influence on performance (Borokhovich et al, 1996;Hermalin & Weisbach, 1988). Recently, the composition of the board has become a key area of interest among governments, researchers, academicians, and debates in public forums because of the benefits associated with the availability of diversified board members in the organizations Kilic (2015). Agency theory argues that outside directors in the board hold the advantage of monitoring the management to keep their reputation as independent and efficient decision makers (Fama & Jensen, 1983).…”
Section: Board Composition and Performance Of Bankmentioning
confidence: 99%
See 1 more Smart Citation
“…Francouer et al (2008) juga membenarkan bahwa keberadaan wanita pada wanita pada bisnis secara eksplisit hanya untuk meningkatkan kebijakan perusahaan. Berbeda halnya dengan beberapa peneliti terdahulu yang menyatakan bahwa keberadaan wanita memiliki pengaruh negatif dan signifikan, diantaranya Darmadi (2011), Adams dan Fereira (2009), dan Kilic (2015).…”
Section: Metodeunclassified
“…Diversitas dewan berpengaruh terhadap kinerja perusahaan (Tu, et al, 2015;Kilic, 2015;Shafique, 2014;Van der Walt, et al, 2006). Ruigrok et al, (2007) …”
Section: Hipotesisunclassified